95 Identification Of Likely Pathogenic Variants In Patients With Bicuspid Aortic Valve: Correlation Of Complex Genotype With A More Severe Aortic Phenotype. (31st May 2014) - Francis, Catherine; Prapa, Stamatia; Abdulkareem, Nada; John, Shibu; Buchan, Rachel; Barton, Paul; Jahangiri, Marjan; Athanassios Gatzoulis, Michael; Pepper, John; Cook, Stuart A
Abstract : Introduction: The common heritable condition of Bicuspid Aortic Valve (BAV) is phenotypically heterogeneous, with valve dysfunction and aortopathy the major complications. We report overrepresentation of rare, likely pathogenic variants in target genes in a large cohort of 176 patients with BAV. We also describe a more severe aortic phenotype in patients with more than one known or likely pathogenic variant, supporting a multi-hit hypothesis for development of complications of BAV. Methods: We recruited 176 patients with BAV without known syndromic basis from two large tertiary referral centres. Phenotyping was performed with routine clinical MRI and/or echocardiography. We identified 63 genes of interest with known or suspected links to BAV or to aortic /aortic valve (AV) pathology. We used genomic DNA from our patients for NGS of these target genes. Control populations were provided by the Exome Variant Server (EVS; 6503 samples) and 1000 genomes project. We analysed called variants in silico, usingSIFT, Polyphen2, Grantham scoring and phastCONS, and categorised variants into the following groups based on likely pathogenicity using a combination of in silico tools: known links with disease, likely, possible, and unlikely pathogenicity. Results: 10 patients (5.7% of our cohort) had variants previously associated with aortic or AV pathology or with abnormalities of smooth muscle function; 3 in GATA5, 2 in FBN1, 2 in MYH11, 1 in NOTCH1 and 1 in COL3A1. In silico analysis identified 45 further instances of 31 likely pathogenic, rare variants in 33 patients (a further 19% of our cohort), in 11 different genes: GATA5 (see Table 1), NOTCH1 (see Figure 1 ), MYH11, PLOD3, FBN1, MMP9, NKX2–5, JAG1, ACE, ENG, PDIA2 and KCNJ2. The combined prevalence of these known or likely pathogenic variants in our cohort was significantly greater than in the EVS control populations (p < 0.0001). 10 patients had known or likely pathogenic variants in more than one gene of interest. These 10 patients had a significantly higher prevalence of significant aortopathy and/or coarctation of the aorta than the rest of our cohort (6/10 vs 20/176; p = 0.0006). Conclusions: We identified known or likely pathogenic genetic variants in nearly a quarter of our BAV cohort. Some of these (eg the c.698T >C variant in GATA5) may be common polymorphisms, wrongly classified by in silico tools. However, many are undoubtedly genuine determinants of phenotype, as evidenced by their overrepresentation in our cohort, and the finding of a more severe aortic phenotype in patients with more than one presumed pathogenic variant. Further research, including our own control population and family studies, is planned. This is also the first study, to our knowledge, to correlate BAV aortopathy with more complex genotypes, and lends support to a multi-hit genetic hypothesis for development of aortic complications of BAV.